SNIIC: a plataforma digital de cultura brasileira sob a perspectiva das convergências entre o Design e a Ciência da Informação - Silva, Anahi Rocha [UNESP] (2016)
The National System of Information and Cultural Indicators (SNIIC) is a digital platform created by the federal government as a tool for the National Culture Plan, with the aim to map and aggregate in a single database, information related to Brazilian culture. It is a dynamic environment information that meets complex system characteristics, convergent, hybrid, and that presents great challenges for its implementation and enforcement. In this sense we propose to analyze the SNIIC from the perspectives of Information Science and Information Design establishing the general objective of identifying resources and subsidies that increase the possibilities of access, sharing and appropriation of information. The research is classified as literature, exploratory, theoretical and applied, since it starts from a literature survey in order to understand and contextualize the information systems and cultural indicators and thus outlining the problem; It is exploratory because it has the platform itself as an object for data collection, research and analysis; theoretical and applied, it aims to establish a product / service to improve the system of search and information retrieval. The test results confirmed the great potential of the platform, but had some problems, such as deficiencies in documentary production and search and information retrieval system. The first pointed problem can be fixed with archival policy adoption and digital curation, with methods and procedures related to the processing of electronic archival documents to correct these deficiencies in document production; already with respect to the second, indicate the practical application of a thesaurus on converted the model Simple Knowledge Organization System (SKOS) standard Resouce Description Framework (RDF), with a view to the organization, retrieval and interoperability between different information and Semantic Web systems, allowing the user to perform queries using their vocabulary in common use, thus providing greater accessibility to information maintained by SNIIC.